2003
DOI: 10.1029/2002tc001377
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic definition of crustal fragmentation and Quaternary block rotations in the east Ventura Basin and San Fernando valley, southern California

Abstract: Paleomagnetic studies of the Pliocene‐Quaternary Saugus Formation in the eastern part of the western Transverse Ranges of California show that the crust is fragmented into small domains, tens of kilometers in linear dimension, identified by rotation of reverse‐fault blocks. In an area approximately 35 × 25 km in the San Fernando valley and east Ventura Basin we identified four distinct domains. Two domains, southwest of and adjacent to the San Gabriel fault, are rotated clockwise: (1) The Magic Mountain domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…New paleomagnetic results reported here from Oligocene and early Miocene sedimentary beds in the Santa Monica Mountains strengthen the argument for large‐scale rotation of the western Transverse Ranges, originally postulated from observations of basement structure trends [ Hamilton and Myers , 1966; Jones et al , 1976] and subsequently supported by paleodeclination data from Eocene and younger rocks [ Kamerling and Luyendyk , 1979, 1985; Hornafius et al , 1986; Levi et al , 1986; Levi and Yeats , 2003; Liddicoat , 1990, 2001; Prothero et al , 1996]. Their paleomagnetic data indicate that post‐Oligocene rotation amounts to 70°–110° clockwise, affecting the northern Channel Islands, Santa Monica Mountains, Santa Ynez Mountains, and areas between (Figure 1).…”
Section: Introductionsupporting
confidence: 86%
“…New paleomagnetic results reported here from Oligocene and early Miocene sedimentary beds in the Santa Monica Mountains strengthen the argument for large‐scale rotation of the western Transverse Ranges, originally postulated from observations of basement structure trends [ Hamilton and Myers , 1966; Jones et al , 1976] and subsequently supported by paleodeclination data from Eocene and younger rocks [ Kamerling and Luyendyk , 1979, 1985; Hornafius et al , 1986; Levi et al , 1986; Levi and Yeats , 2003; Liddicoat , 1990, 2001; Prothero et al , 1996]. Their paleomagnetic data indicate that post‐Oligocene rotation amounts to 70°–110° clockwise, affecting the northern Channel Islands, Santa Monica Mountains, Santa Ynez Mountains, and areas between (Figure 1).…”
Section: Introductionsupporting
confidence: 86%
“…The Saugus sites at Soledad Canyon and the Merrick syncline have predominantly reverse polarity, and each section contains several normal intervals. By analogy with the Magic Mountain and Van Norman Lake sections, Levi and Yeats (2003) concluded that the Saugus Formation in Soledad Canyon and the Merrick syncline was deposited during the Matuyama chron, sometime between 2.6 and 0.78 Ma. In addition to normal and reverse polarity, most of the sites of the Saugus Formation retained stable magnetic remanence with accurate paleomagnetic direc-on August 5, 2015 geology.gsapubs.org Downloaded from tions (declination and inclination) Yeats, 1993, 2003).…”
Section: Summary Of Paleomagnetic Resultsmentioning
confidence: 99%
“…This is considered the main reason for clockwise rotations of many formations west of the San Andreas fault, from the Gulf of California to San Francisco (see references in Levi and Yeats, 2003). The study area is west of the San Andreas fault in the Big Bend region between latitudes 34Њ and 35ЊN ( Fig.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…However, we do not subscribe to the view that, in the brittle upper crust of plate boundary zones, relative plate motion is partitioned, generally, into the relative motion of very large rotating TRANSTENSION IN THE BRITTLE FIELD 195 blocks such that relative motion occurs almost wholly on large displacement faults that bound large rigid blocks (Yeats, 1981;McKenzie and Jackson, 1983;Nur et al, 1986;Nur, 1996, Levi andYeats, 2003). The neotectonics of western North America conforms well to the McCaffrey (2005) model of plate boundary zone behavior with rigid blocks at many scales in a deforming sea of "continuum rubble" at small scales with a wide variety of displacement, strain, and rotation rates, perhaps following a fractal pattern (Turcotte, 1986;Wu, 1993;Marrett et al, 1999).…”
Section: Outline Neotectonics Of Western North America: the Backgroundmentioning
confidence: 93%
“…Only exceptionally will there be a retreating subduction zone, or fluid igneous body into which escape is possible that will allow blocks to remain rigid. Most models of brittle deformation are based on sets of fault-bounded rigid crustal blocks that do not change shape (Yeats, 1981;McKenzie and Jackson, 1983;Nur et al, 1986;Ron and Nur, 1996;Levi and Yeats, 2003), and that have difficulty reconciling strain compatibility issues such as gaps, overlaps, tilting, and zone boundary constraints. In transtension, zones of shortening, elongation, and rotation produce blocks and structures that form in an initial orientation, and then may be simultaneously shortened and/or elongated, rotated out of a favorable orientation to accommodate strain, and then superimposed by newer structures (Dewey, 2002).…”
Section: The Brittle Regime: Problems Of Non-coaxial Deformationmentioning
confidence: 99%